DISSERTATION - KIRUNDA MEDY (UCU, 2024)
ABSTRACT. Using Uganda Christian University as a case study, this study looked at the limitations impacting procurement procedures in private companies and how they affect operational effectiveness. The study focused on budgetary limitations, organizational design, and regulatory compliance. Budgetary restrictions were observed to frequently result in trade-offs between cost and quality, which had an impact on decision-making and procurement schedules. It was discovered that the organizations decentralized procurement procedures contributed to delays and inefficiencies. In addition, it was observed that delays were introduced by legal compliance and regulatory requirements because of the stringent documentation and approval procedures. The study aimed at identifying these constraints and evaluate their impact on procurement performance to suggest ways to improve procurement practices. Using a cross-sectional design, the study combined quantitative and qualitative methods, gathering data through questionnaires, interviews, and observations from a sample of 44 employees out of a total population of 655, selected via stratified sampling. Primary data was collected through direct observations and structured and semi-structured interviews. The study ensured validity by maintaining a Content Validity Index (CVI) of at least 0.70 and upheld reliability through consistent data analysis methods.In chapter four, the data collected is presented, analyzed, and interpreted using tables, pie charts, and bar graphs. Key findings reveal that budgetary limitations lead to compromises in procurement quality and efficiency, while the organizational structure affects the implementation of strategic procurement initiatives. Although regulatory compliance is crucial, it adds to delays and inefficiencies. The study's significance lies in its potential to improve cost efficiency and procurement practices at Uganda Christian University, offering insights that could lead to substantial savings and enhanced organizational outcomes. The research is geographically focused on Uganda Christian University's main campus in Mukono, Uganda, and spans a period of three months. Anticipated limitations include respondent availability and potential reluctance to share information, which will be managed through careful planning and confidentiality assura
THE CONSTRAINTS OF PROCUREMENT IN PRIVATE ORGANISATIONS: WITH A CASE STUDY OF UGANDA CHRISTIAN UNIVERSITY